2011
DOI: 10.1002/polb.22243
|View full text |Cite
|
Sign up to set email alerts
|

Role of balanced charge carrier transport in low band gap polymer:Fullerene bulk heterojunction solar cells

Abstract: Lowering of the optical band gap of conjugated polymers in bulk heterojunction solar cells not only leads to an increased absorption but also to an increase of the optimal active layer thickness due to interference effects at longer wavelengths. The increased carrier densities due to the enhanced absorption and thicker active layers make low band gap solar cells more sensitive to formation of space charges and recombination. By systematically red shifting the optical parameters of poly[2-methoxy-5-(3 0 ,7and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 24 publications
5
45
0
Order By: Relevance
“…In OSCs, the charge carrier mobility is an important factor to optimize: both high mobility and a balance between electron and hole mobilities were shown to be beneficial. 36,[38][39][40][41] For some polymers, an increase in crystallinity is also generally accompanied by a modification in their UV-visible absorption spectra. For example, P3HT exhibits a red shift and the appearance of additional vibronic bands when the degree of crystallinity increases in the BHJ.…”
Section: Effects Of the Morphology On Efficiencymentioning
confidence: 99%
“…In OSCs, the charge carrier mobility is an important factor to optimize: both high mobility and a balance between electron and hole mobilities were shown to be beneficial. 36,[38][39][40][41] For some polymers, an increase in crystallinity is also generally accompanied by a modification in their UV-visible absorption spectra. For example, P3HT exhibits a red shift and the appearance of additional vibronic bands when the degree of crystallinity increases in the BHJ.…”
Section: Effects Of the Morphology On Efficiencymentioning
confidence: 99%
“…In general, among all of the three device performance parameters, FF is the most sensitive one, which is closely related to the bulk properties of the photoactive layer and the interfacial properties between each layer. Specifically, as revealed by many experimental works and device modeling studies [14,15], the FF of PSCs is primarily limited by the charge carrier transporting/collection properties [15,16], charge recombination [17][18][19], and space charge effects [20,21], where charge carriers mobilities [22][23][24][25] and the balance between them [26] play important role. Recently Guo et al demonstrated high FF (up to 80%) in PSCs by using highly ordered polymer with enhanced hole mobility on the order of 10 À3 cm 2 /V s as electron donor [27], highlighting the importance of hole mobility [28] and optimized film morphology in PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the proper choice of solvent or solvent mixtures is one of the important factors for tailoring the film morphology for facilitating the charge transport and enhancing the efficiency of the fabricated devices. In earlier reports, influence of film morphology on photovoltaic response of MDMO PPV in combination with various acceptors has been widely investigated . Even though, very limited information is available on the basic mechanisms of charge transport in pristine MDMO PPV thin films cast in different solvents .…”
Section: Introductionmentioning
confidence: 99%